2017
DOI: 10.1111/jai.13509
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between total length and otolith measurements for 36 fish species from Gökçeada Island, Turkey

Abstract: The relationships between fish total length and otolith measurements (OL, OW and OR) were described by means of allometric power equation for 36 fish species from Gokceada Island, Turkey. Regressions were also estimated at genus level. A total of 14364 specimens were collected monthly using beach seine (0-2 m) and beam trawl (5-20 m) from June 2013 to June 2014. Generally, the otolith length showed the highest correlation for predicting fish total length. This paper represents the first relationships between o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…(2013) and Erdoğan and Torcu-Koc (2016). Finally, Altin and Ayyildiz (2017) and Bilge et al . (2018) studied the relation between the body size and four otolith parameters of this species.…”
Section: Introductionmentioning
confidence: 94%
“…(2013) and Erdoğan and Torcu-Koc (2016). Finally, Altin and Ayyildiz (2017) and Bilge et al . (2018) studied the relation between the body size and four otolith parameters of this species.…”
Section: Introductionmentioning
confidence: 94%
“…DFO [22] identified an unknown number (described as "many") of the 48 predated smolt based on the occurrence of otoliths in stomach contents of the striped bass. Identifying fish species in diets using otoliths is possible [76], but it can be complicated as otoliths are subject to erosion in the gut [77,78]. Identifying otoliths in diet studies requires protocols that include reference collections and/or atlases to address otolith erosion and double counting [77,79].…”
Section: Beland Et Al 2001: Striped Bass Predation Upon Atlantic Salmentioning
confidence: 99%
“…Growth data of D. vulgaris are crucial for the development of proper management strategies, yet many biological aspects of this species remain unknown (Pauly 1983), with most age and growth studies focusing on adult individuals (Gordoa and Molí 1997, Gonçalves et al 2003, Pajuelo and Lorenzo 2003, Mouine et al 2010, Dulčić et al 2011, Hadj-Taieb et al 2013. Although validations of daily ring deposition (Vigliola 1997, Villanueva andMolí 1997), TL and otolith measurements (Altin and Ayyildiz 2018), spawning dates, and pelagic larval duration (PLD; Macpherson and Raventos 2006, Galarza et al 2009, di Franco et al 2013) have been reported, only one daily growth rate study has been conducted to date (Ayyildiz et al 2015).…”
Section: Introductionmentioning
confidence: 99%